Sistem Pendukung Keputusan Pemilihan SMA Negeri Terfavorit Kota Pematangsiantar Menggunakan Metode MOORA - Ilham, Muhammad; Parlina, Iin; Maulana, Arif; Lubis, Ega Khairunnia; Sari, Sufiana Indah (Universitas Islam Sumatera Utara, 2019)
Decision Support System is a system that can be used in making decisions wisely. Pematangsiantar City has difficulties in determining the favorite public high school, because there are quite a number of public high schools in the city. This study aims to help determine the favorite public high school Pematangsiantar city. Elimination requires several criteria including School Accreditation, Student Graduation Level, Student Number, School Achievement and Educator Staff. The method used in building a decision support system for the selection of favorite public high schools is the Multi-Objective Optimization On The Basic Of Ratio Analyzer (MOORA) method. The final results obtained from this study are ranking of Pematangsiantar City Public High School.